Systematic analysis of Fc mutations designed to enhance binding to Fc-gamma receptors - Geoff Hale; Alastair Douglas Davy; Ian Wilkinson (mAbs)
A critical attribute of therapeutic antibodies is their ability to engage with humoral or cellular effector mechanisms, and this depends on the ability of the Fc region to bind to complement (C1q) or Fc receptors. Investigators have sought to optimize these effects by engineering the Fc region to bind to a greater or lesser extent to individual receptors. Different approaches have been used in the clinic, but they have not been systematically compared. We have now produced a matched set of anti-CD20 antibodies representing a range of variants and compared their activity in cell-based assays for complement-dependent cytotoxicity, antibody-dependent cell-mediated cytotoxicity, and antibody-dependent phagocytosis using a range of individual Fc receptors. We have also compared the thermal stability of the variants by differential scanning fluorimetry (DSF). The results reveal a spectrum of activities which may be appropriate for different applications.